ASIC based recorders of electrophysiological signals - Harrison, Andrew (1995)
The ability of application specific integrated circuits (ASICs) to minimise the size and power consumption of electronic circuitry, makes their application to the design of ambulatory monitoring equipment, an attractive option. To this end, a multi-purpose mixed analogue and digital ASIC has been fabricated and incorporated into both a long-term recorder of adult heart rate (HR) and a recorder of electrophysiological signals.